Development of a symptom menu to facilitate Goal Attainment Scaling in adults with Down syndrome-associated Alzheimer’s disease: a qualitative study to identify meaningful symptoms - Kari Knox; Justin Stanley; James A. Hendrix; Hampus Hillerstrom; Taylor Dunn; Jillian Achenbach; Brian A. Chicoine; Florence Lai; Ira Lott; Sanja Stanojevic; Susan E. Howlett; Kenneth Rockwood (Journal of Patient-Reported Outcomes, 2021)
Abstract Background As life expectancy of people with Down syndrome (DS) increases, so does the risk of Alzheimer’s disease (AD). Identifying symptoms and tracking disease progression is especially challenging whenever levels of function vary before the onset of dementia. Goal Attainment Scaling (GAS), an individualized patient-reported outcome, can aid in monitoring disease progression and treatment effectiveness in adults with DS. Here, with clinical input, a validated dementia symptom menu was revised to facilitate GAS in adults living with Down Syndrome-associated Alzheimer’s disease (DS-AD). Methods Four clinicians with expertise in DS-AD and ten caregivers of adults living with DS-AD participated in semi-structured interviews to review the menu. Each participant reviewed 9–15 goal areas to assess their clarity and comprehensiveness. Responses were systematically and independently coded by two researchers as ‘clear’, ‘modify’, ‘remove’ or ‘new’. Caregivers were encouraged to suggest additional items and recommend changes to clarify items. Results Median caregiver age was 65 years (range 54–77). Most were female (9/10) with ≥15 years of education (10/10). Adults with DS-AD had a median age of 58 years (range 52–61) and either a formal diagnosis (6/10) or clinical suspicion (4/10) of dementia. The initial symptom menu consisted of 67 symptoms each with 2–12 descriptors (589 total). The clinicians’ adaptation yielded 58 symptoms each with 4–17 descriptors (580 total). Of these 580 descriptors, caregivers identified 37 (6%) as unclear; these were reworded, and one goal area (4 descriptors) was removed. A further 47 descriptors and one goal area were added to include caregiver-identified concepts. The final menu contained 58 goal areas, each with 7–17 descriptors (623 total). Conclusions A comprehensive symptom menu for adults living with DS-AD was developed to facilitate GAS. Incorporating expert clinician opinion and input from caregivers of adults with DS-AD identified meaningful items that incorporate patient/caregiver perspectives.